Książki na biurko… nie na półkę… - Krajewska, Anna (Przestrzenie Teorii, 2019)
Reminiscences of Professor Stanisław Jaworski, who often joked that books could be divided into those that are to be read immediately, ‘books for the desk’, and those that can wait, ‘books for the shelf’. Following the death of this eminent scholar and superb editor, the author places all Professor’s Jaworski’s books back on her desk...